Chemotherapy-induced immunogenic cell death in combination with ICIs: a brief review of mechanisms, clinical insights, and therapeutic implications - Li, Chengwei; Qi, Xiaoyan; Yan, Min (Frontiers in Pharmacology, 2025)
The combination of chemotherapy and immune checkpoint inhibitors (ICIs) represents a promising strategy for enhancing the efficacy of tumor immunotherapy. This review elaborates on its mechanisms and clinical significances. Chemotherapy-induced immunogenic cell death (ICD) serves as the foundation of this therapeutic synergy, involving the release of damage-associated molecular patterns (DAMPs) such as calreticulin, ATP, and HMGB1, which enhance immune activation in the presence of ICIs. Clinical trials have demonstrated that this combination approach markedly improves clinical outcomes across multiple tumor types, including non-small cell lung cancer, melanoma, bladder cancer, and triple-negative breast cancer. In clinical practice, this combination is increasingly adopted as a first-line or advanced-stage treatment, often guided by personalized medicine approaches. However, several challenges persist, including the management of treatment-related toxicity, high costs, and the identification of predictive biomarkers.